UPAYA MEMPERKUAT AFFECTIVE COMMITMENT TO CHANGE PEGAWAI KEJAKSAAN NEGERI PASAMAN DI TENGAH DIGITALISASI - M. Reyhan Caesaro Anwar; Laura Syahrul; Harif Amali Rivai (Halu Oleo University, 2024)
The rapid transition toward digital working systems were made possible by a series of converging innovations. Therefore, the readiness and affective commitment of workers to commit have considered as a serious challenge to the organization especially governmanet organization such as National Judiciary Institution. This study aims to enhance worker affective commitment to change in the digitalization era through model mediating readiness for change form transformasional leadership and technostress in National Judiciary representative area Pasaman Barat. By distributing paper questionnaires to 62 workers, this study then analyzed participants responses with assisting Smart-PLS latest version software. Results show that there are fifth research expectation are met, and not to the other two.